(3GdOQ GdeUGf aj SjQI GdeXaQ Sdje NGfs - (3Ydj Hf eMeO GddNej GdGTHjdj GdeZQHj, GdeZQHj,J (B923 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi ENJGQ ef NdbI ai cd bQf cQjekG jLOO gPG GdOjf s
(3fSNI NRGFfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B11s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B57 s
Keywords: (3GdJGQjNs